Carboxymethyl chitosan nanoparticle-modulated cationic hydrogels doped with copper ions for combating bacteria and facilitating wound healing - Li, Yaqin; Lu, Jianping; Shi, Jingru; Zhang, Lingjiao; Mu, Haibo; Cui, Tong (Frontiers in Bioengineering and Biotechnology, 2024)
The simultaneous administration of antibacterial treatment and acceleration of tissue regeneration are crucial for the effective healing of infected wounds. In this work, we developed a facile hydrogel (PCC hydrogel) through coordination and hydrogen interactions by polymerizing acrylamide monomers in the presence of carboxymethyl chitosan nanoparticles and copper ions. The prepared PCC hydrogel demonstrated effective bacterial capture from wound exudation and exhibited a potent bactericidal activity against methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa. Furthermore, slow release of copper ions from the hydrogel facilitated wound healing by promoting cell migration, collagen deposition and angiogenesis. Additionally, the PCC hydrogel possessed excellent biocompatibility and hemostatic properties. The practical effectiveness of PCC hydrogel in addressing bacterial infections and facilitating wound healing was verified using a mouse model of MRSA-induced wound infections. Overall, this work presents a simple yet efficient multifunctional hydrogel platform that integrates antibacterial activity, promotion of wound healing, and hemostasis for managing bacteria-associated wounds.